2021
DOI: 10.3390/pathogens10070810
|View full text |Cite
|
Sign up to set email alerts
|

Equine Herpesvirus Type 4 (EHV-4) Outbreak in Germany: Virological, Serological, and Molecular Investigations

Abstract: Equine herpesvirus type 4 (EHV-4) is enzootic in equine populations throughout the world. A large outbreak of EHV-4 respiratory infection occurred at a Standardbred horse-breeding farm in northern Germany in 2017. Respiratory illness was observed in a group of in-housed foals and mares, which subsequently resulted in disease outbreak. Out of 84 horses in the stud, 76 were tested and 41 horses were affected, including 20 foals, 10 stallions, and 11 mares. Virological investigations revealed the involvement of E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 32 publications
3
30
2
Order By: Relevance
“…Pusterla et al 2011 [ 11 ], as well as Badenhorst et al [ 8 ], note that the months with a higher incidence are usually during fall–winter; Matsumura et al [ 39 ] concluded that infections can become clinically overt year-round. Our outbreak took place during the seasonal change to spring, similarly to a very recent paper on EHV4 outbreak in German horses [ 40 ]. While most reports [ 1 , 2 , 8 ] note that EHV-4 infections are usually inapparent and proceed unnoticed, the outbreak in the Romanian farm had a higher morbidity than expected and led to significant economic losses.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pusterla et al 2011 [ 11 ], as well as Badenhorst et al [ 8 ], note that the months with a higher incidence are usually during fall–winter; Matsumura et al [ 39 ] concluded that infections can become clinically overt year-round. Our outbreak took place during the seasonal change to spring, similarly to a very recent paper on EHV4 outbreak in German horses [ 40 ]. While most reports [ 1 , 2 , 8 ] note that EHV-4 infections are usually inapparent and proceed unnoticed, the outbreak in the Romanian farm had a higher morbidity than expected and led to significant economic losses.…”
Section: Discussionmentioning
confidence: 64%
“…Abortions have rarely appeared in mares infected with EHV-4 [ 50 , 51 , 52 ]; however, in our case, 24.32% of the jennies with clinical symptoms aborted—either due to the virus itself or due to poor conditions. In the most recent paper on an EHV-4 outbreak [ 40 ], the authors have not noted any abortions nor mortality; thus, our outbreak might have involved a different strain or had other external factors that influenced the outcome and might warrant a more in-depth look into genotyping the viral strain.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical signs are fever, serous nasal discharge, malaise, pharyngitis, cough, indigestion, and enlargement of regional lymphnodes. Secondary bacterial infections are not uncommon which worsen the respiratory symptoms leading to pulmonary disease (Pavulraj et al 2021). Horses which already have encountered the virus previously develop antibodies which give some protection and only mild infection occurs in subsequent attacks.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Serologic testing of mares after abortion has little diagnostic value. Recently, peptidebased ELISA has been developed that not only confirms the increasing levels of EHV-1 antibodies in mares but also allow differentiation of EHV-1 and EHV-4 specific antibodies (Pavulraj et al 2021).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation